Geographical thougt: A critical introduction to ideas in geography - Nayak, Anoop; Jeffrey, Alex (London Routledge, 2025)
This new second edition of Geographical Thought remains a clear and accessible introduction to the key ideas and figures in human geography. A renewed focus on climate justice is layered throughout the book seguing into a new chapter on decolonising geography. Each of the chapters has been refreshed using the latest scholarship in the field, cutting-edge theory and contemporary case studies. From animal geographies to Black geographies, the current text is brimming with new theories, concepts and ideas.